The qualitative risk assessment model of riskote decision support system - Mileu, Nelson (2018)
Sendai Framework for Disaster Risk Reduction 2015-2030 identify among other principles that disaster risk reduction requires a multi-hazard approach and inclusive risk-informed decision-making. The development of a harmonized decision support tool to ensure that planning decisions are informed about the hazards affecting a given territory, the vulnerability of different land uses, exposed elements and options available to mitigate risks is crucial in the context of spatial planning. The objective of this paper is to describe the qualitative risk assessment model used in the development of the RiskOTe decision support system (DSS). RiskOTe is a spatial decision support system to assist spatial planning integrating the risk management component at municipal level. The qualitative risk assessment model used in RiskOTe is based on risk matrix that relates consequences and likelihood. Oeiras municipality was used as case study to demonstrate the applicability of the spatial decision support system. The scenarios obtained from the case study show that decision-making integrating risk analysis can be supported on a solid basis of information obtained from the system.